Sosialisasi Pelaksanaan Pilkada Tahun 2020 Bagi Penyandang Disabilitas - Eka Yulyana; Nelly Martini; Arip Solehudin (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2021)
Abstract This community service activity focuses on the 2020 Pilkada for People with Disabilities in East Karawang District. The purpose of this service is for persons with disabilities to know and get information related to the implementation of the 2020 Karawang Regency Pilkada. Conducted with the lecture method, question and answer discussions by visiting some people with disabilities in the East Karawang area, as well as webinars for people with disabilities and village and sub-district government officials in East Karawang, a video was made that was shown to candidates with disabilities who were contesting the Pilkada . The results of the implementation of this service activity are knowing that people with disabilities who are still marginalized, with the socialization carried out providing education for persons with disabilities to be willing and not to be ashamed to participate in giving their voting rights in the 2020 Karawang elections, increasing the motivation of some people with disabilities who have never been want to come to enlightened polling stations to intend to come to give their political rights on election day. Conclusion on the implementation of this service activity is still low attention given by the government and election organizers who embrace all levels of society in terms of political participation, never directly socialization activities to the grassroots level, so this activity is felt to be very helpful for the role of the government and election administrators who only conducted one-time election dissemination for persons with disabilities only through the community of persons with disabilities. It is hoped that the impact of this activity is given motivation to persons with disabilities who have not participated so far, they are eager to come to the polling station to give their voting rights. With direct visits, persons with disabilities feel that their existence is significant in community life. ABSTRAK Kegiatan pengabdian pada masyarakat ini fokus pada Pilkada Bagi Penyandang Disabilitas 2020 di Kecamatan Karawang Timur. Tujuan dari pelaksanaan pengabdian ini adalah agar para penyandang disabilitas mengetahui dan mendapatkan informasi terkait pelaksanaan Pilkada Kabupaten Karawang tahun 2020. Kegiatan ini dilaksanakan dengan metode ceramah, diskusi tanya jawab dengan mendatangi sebagian penyandang disabilitas yang berada di wilayah Karawang Timur, serta webinar untuk penyandang disabilitas dan aparat pemerintah desa dan kecamatan di Karawang Timur, dilakukan pembuatan video yang diperlihatkan kepada kaum disabilitas para calon yang berkontestasi dalam Pilkada. Hasil pelaksanaan kegiatan pengabdian ini adalah mengetahui bahwa para penyandang disabilitis yang masih termarginalkan, dengan sosialisasi yang dilaksanakan memberikan pendidikan bagi penyandang disabilitas untuk mau dan jangan malu berpartisipasi memberikan hak suaranya dalam Pilkada Karawang tahun 2020, meningkatkan motivasi sebagian para penyandang disabilitis yang selama ini tidak pernah mau datang ke TPS tercerahkan untuk berniat datang memberikan hak politiknya pada hari pemilihan. Simpulan atas pelaksanaan kegiatan pengabdian ini masih rendahnya perhatian yang diberikan pemerintah dan penyelenggara Pemilu yang merangkul semua lapisan masyarakat dalam hal partisipasi politik, tidak pernah secara langsung kegiatan sosialisasi sampai pada level akar rumput, sehingga kegiatan ini dirasakan sangat membantu peran pemerintah dan penyelenggara pemilu yang hanya melakukan satu kali sosialisasi pilkada untuk penyandang disabilitas yang hanya melalui komunitas penyandang disabilitas. Dampak dari kegiatan ini diharapkan setelah diberikan motivasi kepada para penyandang disabilitas yang selama ini tidak ikut berpartisipasi, mereka bersemangat untuk datang ke TPS memberikan hak suaranya. Dengan adanya kunjungan secara langsung para penyandang disabilitas merasa keberadaannya pun berarti dalam kehidupan masyarakat.